2010
DOI: 10.1111/j.1751-1097.2010.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Dermatophytes to Photodynamic Treatment with Special Focus on Trichophyton rubrum

Abstract: Owing to the accessibility of skin to light, many applications of photodynamic treatment (PDT) have been developed within dermatology. The recent increase of dermatological antimicrobial PDT investigations is related to the growing problem of bacterial and fungal resistance to antibiotics. This review focuses on the susceptibility of dermatophytic fungi, in particular Trichophyton rubrum, to PDT and shows its potential usefulness in treatment of clinical dermatophytoses. There are no data indicating significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 109 publications
(151 reference statements)
0
56
0
8
Order By: Relevance
“…These antimycotic agents are most effective against the growing organism but are often ineffective against static phases of the organism, such as T. rubrum conidia, leading to reinfection, unless prolonged treatment regimens are adopted. Recently, photodynamic treatments have been developed using photosensitizers in combination with UV-A1 radiation (340 to 400 nm) to kill both the mycelial form and the conidia of T. rubrum (13) in topical dermal infections. The antifungal agents most commonly used against T. rubrum are ketoconazole, fluconazole, terbinafine, and flucytosine (13).…”
mentioning
confidence: 99%
“…These antimycotic agents are most effective against the growing organism but are often ineffective against static phases of the organism, such as T. rubrum conidia, leading to reinfection, unless prolonged treatment regimens are adopted. Recently, photodynamic treatments have been developed using photosensitizers in combination with UV-A1 radiation (340 to 400 nm) to kill both the mycelial form and the conidia of T. rubrum (13) in topical dermal infections. The antifungal agents most commonly used against T. rubrum are ketoconazole, fluconazole, terbinafine, and flucytosine (13).…”
mentioning
confidence: 99%
“…One of the factors that may explain the lack of damage is that the PS did not cross the leaf cuticle. As the reactive species generated during PDT have very short half-lives, their diffusion is limited, and therefore, damage is restricted to structures close to the PS (18). As the PS remained outside the cuticle, which is approximately 4 m thick, the internal leaf structure was not damaged by the PDT.…”
Section: ϫ2mentioning
confidence: 98%
“…APDT has been used to treat human mycoses caused mainly by fungi of the genera Candida and Trichophyton (15,16,18,29,30). It is thus logical that novel applications of APDT are explored, including its use to control plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous published studies have shown PDT to be highly effective in the in vitro inactivation of fungi (19,20,31). In addition, it is considered that the development of resistance to PDT by microbes is an unlikely event, because PDT is typically a multitarget process, which is a difference between PDT and most other antifungal drugs (22).…”
mentioning
confidence: 99%